Untethering the Queue based on Multi Channel Access (MCA) Technology at Hospital Radiology Section - Dharma Dyatmika; Oka Sudana; Gusti Agung A. Putri (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: Information technology is developing rapidly over time, but there are many companies do not make use of it to support their operational activities. One example is the queue system in the Radiology Section of Sanglah Hospital, which operates the conventional queue system.Objective: The problem occurs in this queue system is inefficient waiting time because the patients must come early and wait in line in the hospital waiting rooms. Many patients thereafter decide going home first or doing other activities. Another problem is it triggers double costs of transportation. The purpose of this study is to improve patients comfort while waiting in queue by applying untethering the queue. Untethering the queue is a service that allows people to be in a queue even though they are not in the waiting room.Methods: The system applies the FCFS (First Come First Serve) algorithm to manage patients’ queue and integrates this queue system with Telegram and SMS gateway. It makes patients easier to take queue numbers and receive notification of health service time from the Radiology Section of Sanglah Hospital.Result:  As a result of this study is an untethering the queue application which is web-based queue system integrated to Telegram and SMS gateway. The daily queue services in the Radiology Section of Hospital can be improved through this application.Conclusion: Patients can only come to the hospital when the queue numbers obtained nearly the health service time so that it leads to time efficient and comfort while waiting in queue.Keywords:First Come First Serve, Multi Channel Access, SMS, Telegram, Untethering the Queue